The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/978-3-319-54910-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and Physiology of Reactive Oxygen Species in Euglena

Abstract: Reactive oxygen species (ROS) such as superoxide and hydrogen peroxide are by-products of various metabolic processes in aerobic organisms including Euglena. Chloroplasts and mitochondria are the main sites of ROS generation by photosynthesis and respiration, respectively, through the active electron transport chain. An efficient antioxidant network is required to maintain intracellular ROS pools at optimal conditions for redox homeostasis. A comparison with the networks of plants and animals revealed that Eug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…Intriguingly, despite their apparent importance, catalases are not essential for life [59] and there are examples of eukaryote organisms lacking these enzymes (e.g. Euglena spp., Neurospora crassa ) [61]. It has, furthermore, been documented that catalase null mice develop normally and do not display any gross physical or behavioral abnormalities [62].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, despite their apparent importance, catalases are not essential for life [59] and there are examples of eukaryote organisms lacking these enzymes (e.g. Euglena spp., Neurospora crassa ) [61]. It has, furthermore, been documented that catalase null mice develop normally and do not display any gross physical or behavioral abnormalities [62].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike non-selenium GPXs from Chlorophyta, non-selenium GPX isolated from E. gracilis uses GSH as an electron donor [111]. In addition to GSH-dependent GPX, the transcriptome data of E. gracilis indicated the existence of three putative Trxdependent GPXs [112].…”
Section: Glutathione Functions 421 Glutathione Peroxidasementioning
confidence: 99%
“…Its biosynthesis is catalyzed by two distinct enzymes: glutathionylspermidine (GSP) synthetase (GSPS) conjugates the first GSH molecule to spermidine, and trypanothione synthetase (TRYS) adds the second GSH molecule to GSP (Figure 4) [128]. Transcriptome data showed that E. gracilis contains two highly homologous genes to GSPS and TRYS genes from trypanosomatid Crithidia fasciculata [112]; however, these genes have not yet been functionally characterized.…”
Section: Glutathione Derivative Trypanothionementioning
confidence: 99%
See 1 more Smart Citation
“…These genes are also absent or nonfunctional in trypanosomatid parasitic protists, such as Leishmania [25]. In addition, Trypanosomatids produce the unusual GSH molecule trypanothione and express trypanothione-dependent reductase and peroxidase enzymes that function analogously to GR and GPX in trypanothione redox cycling [26,27]. Insects largely lack the GR and GPX genes and so, although they rely on the GSH redox cycle, GSH is regenerated via the TRX system rather than GR.…”
Section: Introductionmentioning
confidence: 99%